B cell activating factor (BAFF) from neutrophils and dendritic cells is required for protective B cell responses against Salmonella typhimurium infection - Runa Kuley (Public Library of Science (PLoS), 2021)
Mice lacking B cells are more susceptible to S. typhimurium infection. How B cells contribute to protective immunity against Salmonella and what signals drive their activation are still unclear. Neutrophils (Nphs), monocytes (MOs), and dendritic cells (DCs) are involved in early immune responses to control the initial replication of S. typhimurium. These cells can produce B cell activating factor (BAFF) required for mature B cell survival and may help regulate B cell responses during Salmonella infection. Using BAFF reporter mice (BAFF-RFP+/-), we discovered that an i.p. infection with a virulent strain of S. typhimurium increased BAFF expression in splenic conventional DCs (cDC) and inflammatory Ly6Chi MOs/DCs four days post-infection. S. typhimurium infection induced the release of BAFF from Nphs, a decrease of BAFF-RFP expression and expansion of BAFF-RFP+ Nphs in the spleen and peritoneal cavity. After S. typhimurium infection, serum BAFF levels and immature and mature B cell subsets and plasma cells increased substantially. Conditional knockout (cKO) mice lacking BAFF in either Nphs or cDCs compared to control Bafffl/fl mice had reduced up-regulation of systemic BAFF levels and reduced expansion of mature and germinal center B cell subsets after infection. Importantly, the cKO mice lacking BAFF from either Nphs or cDCs had impaired induction of Salmonella-specific IgM Abs, and were more susceptible to S. typhimurium infection. Thus, Nphs and cDCs are major cellular sources of BAFF driving B cell responses, required for mounting optimal protective immunity against lethal Salmonella infection.